Pesticide Applicator CEU Opportunities via the UF/IFAS Pesticide Information Offices On-Line Interactive Tutorials - Frederick M. Fishel; Jason A. Ferrell (EDIS)
PI-144, a 4-page illustrated fact sheet by Fred Fishel and Jason Ferrell, describes the development of interactive tutorials for pesticide applicator CEU credit, includes information on how to purchase then and submit the files for approval. Published by the UF/IFAS Pesticide Information Office, January 2007.